Sports in Early Childhood for Optimal Holistic Development: A Comprehensive Exploration of MKSE: Olahraga pada Anak Usia Dini untuk Perkembangan Holistik Optimal: Eksplorasi Komprehensif MKSE - Arifin Mado (Academia Open, 2024)
The purpose of this study was to find out how an understanding of sports activities affects the overall development of young children, with a focus on motor development, cognitive, social and emotional well-being. The research was conducted through a mixed approach by conducting qualitative interviews, direct observations, and quantitative surveys with children, parents, and teachers. The results showed that children's motor development, cognitive progress, social skills and emotional well-being were positively correlated with children's sports understanding. This study has practical consequences, including the suggestion that sports activities should be incorporated into early childhood education to enhance their overall growth. This study provides the basis for a more comprehensive approach to education, providing a better understanding of the role of sport in optimizing children's development in the early stages of their development. Highlights: Holistic Influence: Examining sports understanding's broad impact on early childhood development, encompassing motor skills, cognition, and socio-emotional well-being. Robust Analysis: Employing qualitative interviews, direct observations, and quantitative surveys with children, parents, and teachers to provide a multifaceted understanding of the relationship. Educational Integration: Positive correlations between sports comprehension and motor development, cognitive progress, social skills, and emotional well-being underscore the need for incorporating sports activities into early childhood education. Keywords: Early Childhood, Sports Understanding, Holistic Development, Motor Skills, Cognitive Progress